1997
DOI: 10.1359/jbmr.1997.12.4.616
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Secretion of Parathyroid Hormone in Postmenopausal Women: Assessment by Deconvolution Analysis and Approximate Entropy

Abstract: In healthy young subjects, parathyroid hormone (PTH) is secreted presumptively in a dual fashion, with low amplitude pulses apparently superimposed on tonic secretion. In contrast, PTH secretion has not been as well characterized in postmenopausal women, and relationships among bone density, estrogen status, and PTH release have not been explored. It is possible that a pulsatile pattern of PTH secretion is important for bone remodeling, since exogenous PTH administered in a pulsatile manner stimulates bone for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Studies addressing pulsatile variation of PTH are summarised in Supplemental Data Table 9 [68,76,79,[93][94][95][96][97][98][99][100][101][102].…”
Section: Pulsatile Variationmentioning
confidence: 99%
“…Studies addressing pulsatile variation of PTH are summarised in Supplemental Data Table 9 [68,76,79,[93][94][95][96][97][98][99][100][101][102].…”
Section: Pulsatile Variationmentioning
confidence: 99%
“…One reason for these contradictory results may be due to the fact that single random measurements do not reflect the overall pattern of PTH secretion in a given subject nor do they give any insight into possible abnormalities in the secretory dynamics of PTH as a consequence of the glucocorticoids. This point is particularly relevant since it is now known that PTH is secreted both in low amplitude pulses and in a tonic secretory state (16,17). Until the results of this study, no comparable data were available on pulsatile vs tonic secretory PTH dynamics in patients chronically treated with glucocorticoids.…”
Section: Discussionmentioning
confidence: 91%
“…In healthy individuals, pulsatile PTH secretion accounts for approximately 25% of the total secreted PTH (15). No significant differences in these secretory dynamics have been observed between normal men and women (16) nor have there been any significant correlations between these patterns and the ambient PTH or ionized calcium concentration (17). In a disorder such as postmenopausal osteoporosis, however, dampened PTH pulsatility has been reported in some but not all early studies (13,14,17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have established that in healthy young subjects, PTH secretion has two major components: a predominantly tonic pattern of constant secretion and low amplitude pulses with high frequency (approximately every 15-20 minutes). In healthy individuals, pulsatile PTH secretion accounts for approximately 25% of the total secreted PTH 49,50 . We have recently found that PTH secretory dynamics are altered by glucocorticoids with a reduction in the tonic component and an exaggeration in the pulsatile component of PTH secretion that override normal secretory dynamics 51 .…”
Section: Gcs and Bone Resorptionmentioning
confidence: 99%